La búsqueda de la armonía en la diversidad : el diálogo ecuménico e interreligioso desde el Concilio Vaticano II - Pérez Prieto, Victorino; Melloni, Javier, 1962- (Estella (Navarra), España : Editorial Verbo Divino, 2014)
Interreligious dialogue is increasingly necessary in a world of religious and cultural pluralism. This dialogue is not new; however, as indicated in the Prologue by J. Melloni, is still a virgin territory to explore, which is necessary to combine fidelity to one's own tradition and at the same time, oen to the mystery of God, the human being and the world from what is experienced in other traditions. This joint is difficult which this book aims.
El Concilio Vaticano II, un nuevo comienzo para la Iglesia, sin anatemas ni descalificaciones, sino en diálogo con todos los cristianos y las demás religiones -- El diálogo ecuménico e interreligioso en los documentos del Concilio -- La unidad en la diferencia y la 'armonia invisible', verdadero reto del diálogo ecuménico e interreligioso -- El diálogo interreligioso : un ecumenismo-ecuménico en un diálogo-dialogal... sin olvidar a los pobres ni a las mujeres -- El diálogo intrarreligioso : la pertenencia religiosa múltiple -- Un colofón que busca ir cargado de fe, esperanza y amor.
Includes bibliographical references.
Online resource; title from ePub cover page (Digitalia, viewed July 15, 2016)
Keywords: Ecumenical movement; Interdenominational cooperation; Electronic books